PENGARUH EKSTRAK EDAMAME KAYA GENISTEIN TERHADAP KADAR LOW DENSITY LIPOPROTEIN, HIGH SENSITIVITY-C REACTIVE PROTEIN, SERTA RASIO NEUTROFIL LIMFOSIT DAN MONOSIT LIMFOSIT: Studi Experimental pada Tikus Jantan yang Diinduksi Aterosklerosis - Pratama, Reza Dian; Maharani, Nani; Bahrudin, Udin (Medica Hospitalia : Journal of Clinical Medicine, 2021)
ABSTRACT Background: Atherosclerosis is related to hypercholesterolaemia and inflammation. Edamame is one of the soybeans with high levels of genistein which protects the formation of atherosclerosis. Purpose: This research aimed to evaluate the effects of genistein-rich edamame on LDL, hs-CRP, Neutrophil-Lymphocyte Ratio (NLR) and Monocyte-Lymphocyte Ratio (MLR) on atherosclerosis-induced mice. Method: This research is a true experimental study with posttest only-controlled group design. Thirty male rats were divided randomly into five groups: negative control group without any intervention, positive control group with atherosclerosis induction, first intervention group with edamame extract supplementation, second intervention group with genistein-rich edamame extract supplementation, and third intervention group treated with atorvastatin. After 28 days, serum LDL, hs-CRP, LDL and MLR were measured. Results: There were significant differences (p<0.001) of hs-CRP values between the second intervention group compared to the negative control, positive control and first intervention group. Edamame extract lowered LDL cholesterol levels in the second intervention group compared to positive control, but the difference were not statistically significant. There were significant differences (p<0.05) of MLR values between the second intervention group and the negative control and also the first intervention group, and significant differences between the second intervention group and the negative control and also the first intervention group. There was no significant difference on NLR values between all groups. Conclusion: The administration of genistein rich edamame may reduces the inflammation in the blood vessels better than edamame extract represented by lower hs-CRP and MLR values compared to the edamame extract. Keywords: Genistein rich-edamame, LDL, hsCRP, neutrophil-lymphocyte ratio, monocyte-lymphocyte ratio